2016
DOI: 10.1080/08870446.2016.1240173
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods process evaluation of a goal management intervention for patients with polyarthritis

Abstract: Process evaluations of newly developed interventions are necessary to identify effective and less effective intervention components. First aim of this study was to identify key components of a psychosocial goal management intervention from the perspective of participants, and second aim was to evaluate the intervention's fidelity. A mixed-methods approach was applied to 24 interviews with participants post-intervention and 16 audio recordings of random training sessions. Participants experienced three key comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Evidence from RCTs also showed that nurse-led care improved patient activation, self-efficacy for physical activity and motivation, as well as patients’ self-assessment 7 11 34 35. A recent cohort study and several descriptive studies found that nurse-led interventions enhanced patients’ confidence in facilitating their daily life, behavioural change and coping with disease fluctuations 47–49 67 78–80. The TF discussed the terms ‘empowerment’ and ‘sense of control’, which were used in the former recommendation No 6 (online supplementary table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from RCTs also showed that nurse-led care improved patient activation, self-efficacy for physical activity and motivation, as well as patients’ self-assessment 7 11 34 35. A recent cohort study and several descriptive studies found that nurse-led interventions enhanced patients’ confidence in facilitating their daily life, behavioural change and coping with disease fluctuations 47–49 67 78–80. The TF discussed the terms ‘empowerment’ and ‘sense of control’, which were used in the former recommendation No 6 (online supplementary table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Aims of the mixed methods studies (n = 11) could be broadly categorized as: intervention development (Arends et al, 2015(Arends et al, , 2017Scobbie et al, 2011), process evaluation (Lyons et al, 2018;McPherson et al, 2009;Scobbie et al, 2013); understanding the process of goal adjustment in different long-term conditions (Boerner & Cimarolli, 2005;Boerner & Wang, 2012;Crombez et al, 2016;Hoyt et al, 2016) and investigating goal setting issues in neurological rehabilitation (Playford et al, 2009).…”
Section: Mapping Of Goal Adjustment Literaturementioning
confidence: 99%
“…Evaluating the effectiveness of other interventions reported to support goal adjustment within our reviewthe Goal setting and Action Planning framework (Scobbie et al, 2011(Scobbie et al, , 2013; SMARTER goal setting framework (Hersh et al, 2012); Right on Target (Arends et al, 2013(Arends et al, , 2017(Arends et al, , 2018 and the Health Through Activity programme (Lyons et al 2018) could go some way to addressing this evidencepractice gap. Our findings also suggested candidate psychological interventions that may be worthy of further development and evaluation includingmindfulness; cognitive behaviour therapy, motivational intervening and acceptance and commitment therapy.…”
Section: Mapping Exercisementioning
confidence: 99%
“…Parallel to the present study, an in-depth process evaluation of Right on Target was executed [56]. Adherence to the protocol was found to be satisfactory, indicating that the intervention was executed as intended.…”
Section: Positive Affect Follow-up (T3)mentioning
confidence: 77%